Investigating the Effect of Ball Milling and Heating Processes on the Phase Changes of an Iranian Type of Bauxite - H. Haddady; N. Setoudeh; A. Mohassel; R. Hayati (Journal of Advanced Materials in Engineering)
The bauxite samples were prepared from the resources of Kohgiluyeh and Boyer-Ahmad province, Iran. The chemical and mineralogical compositions were determined after crushing of the specimens. The ball milling of the bauxite samples was done via a planetary ball mill in both steel and zirconia cups.  The isothermal heating was performed in the temperature range of 600-1000˚C for one hour under the air atmosphere. The boehmite phase was observed as the major mineral in the XRD patterns of the bauxite sample. The calcination (dehydration) temperature of the bauxite sample containing boehmite mineral was determined at ~540˚C using STA analysis. The boehmite phase of the bauxite sample was decomposed into aluminum oxide after heating, and the weight loss of the heated products caused by this phase transition was in the range of L.O.I in the chemical analysis. After heating of the milled bauxite samples at 800˚C, the traces of aluminum oxide were detected in the XRD patterns. The overlapping of the major peaks of aluminum oxide and magnetite phase in the XRD patterns was the reason to perform the VSM analysis. The VSM results confirmed the signs of a magnetic phase in the as-milled bauxite samples. The results of this research indicated that either the presence of iron impurities due to the abrasion of the chamber wall and the balls during the milling of the bauxite sample in the steel cup or the presence of the ferrous iron in the bauxite sample could be the origin of the magnetic sings. These items are also the main reasons for appearance of the magnetite phase.